Peningkatan keterampilan kewarganegaraan peserta didik dengan penerapan model problem-based learning berbasis e-LKPD interaktif - Faridhotul Alfiyah Mukhlisotin; Fahdian Rahmandani (Universitas Muhammadiyah Malang, 2023)
Improving students’ citizenship skills through problem-based learning model with interactive e-LKPD. One indicator of the success of government is community participation. Community participation in government is included in citizenship skills. However, unfortunately the level of participation of the Indonesian people is still low. This study aims to improve students' citizenship skills in the Pancasila Education subject. This research is a classroom action research. The research subjects were students of class X-7 Senior High School 1 of Batu. Data collection uses methods using observation, tests and questionnaires. The data obtained were analyzed using descriptive statistics. The results of the study show the following: (a) the application of the PBL model with interactive e-LKPD on learning outcomes analyzing the rights and obligations of citizens regulated in the 1945 Constitution of the Republic of Indonesia increases cognitive citizenship skills by 17% and cognitive citizenship skills by 21% (b) as many as 30 or 86% of students were included in the successful category in achieving cognitive citizenship skills and as many as 31 or 88% of students were included in the successful category in achieving participation citizenship skills in cycle II.